2011
DOI: 10.1176/ps.62.5.pss6205_0477
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Initiatives to Reduce Seclusion and Restraint in a State Psychiatric Hospital

Abstract: These data suggest that substantial reductions in use of seclusion and restraint are possible in inpatient psychiatric settings and that changes to the physical characteristics of the therapeutic environment may have a significant effect on use of seclusion and restraint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 34 publications
0
109
1
3
Order By: Relevance
“…A recent study reported on a staged implementation of four strategies to reduce the use of seclusion and restraint (Borckardt et al . ). Therapeutic environmental changes was the only strategy found to be significantly correlated with the observed reductions in seclusion and restraint use, thought to be in part due to providing a constant reminder about the need to change practice.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported on a staged implementation of four strategies to reduce the use of seclusion and restraint (Borckardt et al . ). Therapeutic environmental changes was the only strategy found to be significantly correlated with the observed reductions in seclusion and restraint use, thought to be in part due to providing a constant reminder about the need to change practice.…”
Section: Discussionmentioning
confidence: 97%
“…; Borckardt et al . ; Donat ; Donat ; Taxis ). The contrasting findings of our study compared with previous studies might be explained by the fact that, although the involvement of patients in the development of an individualized treatment plan is essential, the methodical work approach comprises more.…”
Section: Discussionmentioning
confidence: 99%
“…In Borckardt et al . 's () study, the involvement of patients in treatment planning was not found to be associated with a reduction in seclusion and restraint. The discrepancy between the axiomatic inclusion of the methodical work approach in the education of Dutch health‐care professionals, and the lack of evidence demonstrating the benefits for patient care, were an incentive for the present study.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Forster and colleagues 26 focused their training on increasing awareness of factors that lead to agitation and violence, teaching less restrictive interventions, and the teaching of safe reactions to patient violence. Borckardt and colleagues 27 implemented an engagement model that includes trauma-informed care training, changes in rules and language, patient involvement in treatment planning, and changes to the physical characteristics of the therapeutic environment. Project BETA believes that the culture that promotes the use of restraint and seclusion can be changed.…”
Section: Use Of Physical Restraintmentioning
confidence: 99%